The Recurrent Myxoma of the Heart - Abdumadzhidov Kh. A; Buranov Kh.Zh (Genius Journals, 2023)
Heart myxomas - primary good good quality tumors _ b died , basically _ heart cameras , in particular k o' pro q left b occupies the die ( ChB ) . Heart of tumors less spread _ _ specialists by confession will be done and they are head q a heart tumors _ q ator 0.0017-0.02% cardial pathology organize reaches
Keywords: Heart; pathology; reaches